ANALISIS PENGARUH P-DELTA EFFECT TERHADAP PERBEDAAN KETINGGIAN STRUKTUR GEDUNG TAHAN GEMPA (STUDI KASUS: NON-HIGHRISE BUILDING) - Istiono, Heri; Ramadhan, Azhar Yusuf (Rekayasa Sipil, 2020)
The need for earthquake resistant buildings in Indonesia is something that needs to be considered. Considering that Indonesia is an earthquake prone area. A building structure must be designed to be able to withstand lateral loads such as earthquakes within the limits set by the code/standards. For conservative reasons analysis of the P-Delta Effect needs to be considered because the building development ratio will always increase every time. according to SNI 1726-2019 the P-Delta effect is only required for the design of tall buildings. In this case, the P-Delta effect will be calculated in the modeling of non-high-rise buildings and get the results that P-Delta Effect increased story forces: moment of the building under 10%.